Modified Backward Chaining Android Application to Diagnose Psychoneurosis and Psychosomatic Disorder - Wibby Aldryani Astuti Praditasari; Eva Novianti; Ikhwannul Kholis; Rian Andriyusadi (IAES Indonesia Section, 2019)
Stress, depression, mental illness are serious problems but the most often overlooked problems. Ironically, the number of mental problems is greater than health services. The purpose of this study is to develop a system consisting of Admin Webpage and Android Application which analyze mental illness with artificial intelligence that can diagnose and carry out therapy for people with mental disorders which has the types of psychoneurosis and psychosomatic disorders. This research used the methodology of Modified Backward Chaining which works backward towards the initial condition of the patient. Moreover, the system used the Expert System as reference data from the expert, in this case, psychologist. Results could be diagnosed via smartphone by a doctor or expert so they could provide faster and easier treatment in accordance with the application of this Psychological PPD (Psychoneurosis and Psychosomatic Disorders). Finally, the application was successfully implemented to give diagnoses and treatments. The system's ability to deal with mental illness was carried out at Raden Mataher General Hospital, Jambi, Indonesia. This study consisted of 21 respondents consisting of 13 men and 8 women. The result showed that the application was tested Usability Testing which had score 4.22 of 5.